PENGARUH IOS DAN PENGUNGKAPAN CSR PADA NILAI PERUSAHAAN DENGAN PERTUMBUHAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Bella, Luh Kadek Githa; Suaryana, I.G.N Agung (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
The establishment of the company's goal to optimize the company's earnings, thereby enhancing the welfare shareholders and its impact on increasing the company's value. This research to know influence of Investment Opportunity Set (IOS) and the disclosure of Corporate Social Responsibility (CSR) in value of company with the company's growth as moderating variables. Non-probability sampling method with purposive sampling technique used in sampling, so acquired 52 companies and generate 156 observasian year period 2013-2015. Mechanical analysis using the interaction test, namely Moderated Regression Analysis (MRA). Based on the analysis, IOS positive effect on the value of the company, CSR has no effect on the value of the company, strengthening the influence the company's growth investment opportunity set the value of the company, as well the disclosure the company's growth weaken corporate social responsibility in value  company.
Keywords: Value companies, IOS, disclosure CSR, company' s growth.